2020
DOI: 10.21512/bbr.v11i1.6082
|View full text |Cite
|
Sign up to set email alerts
|

Monetary and Fiscal Policies Interactions on Stock Returns in Nigeria

Abstract: This research examined the effects of monetary and fiscal policies on stock returns in Nigeria. The researchers utilized ex-post facto research design using the time series data of the annual market values of All Share Index (ASI) of the Nigerian Stock Exchange (NSE). It was yearly data on the various monetary policy and fiscal policy variables obtained from the Central Bank of Nigeria Statistical Bulletins covering from 1985 to 2017. The result of the cointegration test reveals a long-run relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Stock investing and financial performance have not been conclusively linked in the research. Idowu et al (2018) discovered a positive connection between ROA and NPM and an insignificant negative association for EPS for the dependent variable. Saleh (2015), Natarajan et al (2013), Kurnati (2019), Jinadu et al (2018), Herelemina (2017), Ngunjiri (2016), and Kioko and Ochieng' (2020) found a significant positive relationship between stock investment and financial performance, while Jahromi and Jokar (2013) found no relationship.…”
Section: Knowledge Gapmentioning
confidence: 92%
“…Stock investing and financial performance have not been conclusively linked in the research. Idowu et al (2018) discovered a positive connection between ROA and NPM and an insignificant negative association for EPS for the dependent variable. Saleh (2015), Natarajan et al (2013), Kurnati (2019), Jinadu et al (2018), Herelemina (2017), Ngunjiri (2016), and Kioko and Ochieng' (2020) found a significant positive relationship between stock investment and financial performance, while Jahromi and Jokar (2013) found no relationship.…”
Section: Knowledge Gapmentioning
confidence: 92%